Extract characteristics of supercritical carbon dioxide extraction of Nannochloropsis oculata - Douglas, Nathaniel James, author; Willson, Bryan Dennis, 1959-, advisor; Marchese, Anthony John, 1967-, committee member; Johnson, Jerry, committee member; Smith, T. Gordon, committee member (Colorado State University. Libraries, 2011)
This research progresses the understanding of super-critical carbon dioxide extraction of an algal sample composed of Nannochloropsis oculata. The apparatus used in the experiments was optimized in several iterations to find the best balance of quality of data collection and practicality of operation. Thin-layer chromatography (TLC), gas chromatography (GC), and gravimetric analytical techniques were applied to the algae extract. The results indicate that 400 ± 4.5 bar and 83 ± 9.7°C recovered the largest proportion of extract on a mass basis. TLC analysis revealed a polar spot for some experiments, but it was not possible to verify that the spot was from the extraction and not a contaminant. GC analysis verified the lipid profile of the extract was modified by different extraction conditions and over the course of the extraction. The results reveal that additional research is warranted with super-critical carbon dioxide extraction of algae.
Keywords: algae; carbon; dioxide; extraction; nannochloropsis; supercritical